Childhood and Nation: The Meaning of Two Categories in a Globalized World (KULT_online, 2017)
The book Childhood and Nation. Interdisciplinary Engagements, edited by social scientists Zsuzsa Millei (Univ. Tampere, Finland) and Robert Imre (Univ. Newcastle, Australia), discusses questions about childhood and nation within eleven examples from different countries. Thereby, the chapters target issues regarding the difference between children growing up in a globalized world while being raised as national citizens. Consequently, the book elaborates on the tension between the national identification every child is confronted with and the pertinent idea of childhood as a global and cosmopolitical concept. In this respect, migration and statelessness are seen as two conditions questioning nationality in recent times.